Randomized Crossover Study Showing Nurse-Led Same Day Review Replacing Next Day Review in Uneventful Phacoemulsification to Be Safe and Efficacious - Jennifer W. H. Shum; Janice J. J. Cheung; Monica M. N. Lee; Oscar G. W. Wong; Kenneth K. W. Li (Journal of Ophthalmology)
Purpose. To study whether nurse led same-day review (SDR) after uneventful phacoemulsification can replace next-day review (NDR) in terms of safety and efficacy. Setting. Patients are recruited from an ophthalmology outpatient clinic in Hong Kong. Design. A prospective, randomized crossover study conducted from November 2012 to 2014. Methods. Inclusion criteria include cataract surgery naïve patients undergoing phacoemulsification under local anaesthesia. All patients were seen by our ophthalmic nurse 2 hours after surgery. Before undergoing phacoemulsification of the first eye, patients were randomized to be reviewed on day 1 or 7 after surgery. Surgeons and reviewing doctors were blinded to patient allocation. For the patients’ second eye surgery, group allocation will cross over. Primary outcome measures include visual improvement and patient satisfaction questionnaire. Other measures include cataract characteristics, surgical details, and complications. Statistical tests include paired t-test, Wilcoxon signed rank test, and Chi-square test. Results. 164 eyes from 82 patients were available. Visual improvement, satisfaction, and complications were comparable between both groups. Conclusions. A nurse led SDR can replace NDR in uneventful phacoemulsification in terms of safety and efficacy. Patient satisfaction is also comparable in the setting of Asian culture and when transportation is not a major concern.